Abhorsen - Nix, Garth (New York, N.Y. : Eos, 2004)
Abhorsen-In-Waiting Lirael and Prince Sameth, a Wallmaker, must confront and bind the evil spirit Oranis before it can destroy all life.
Sequel to: Sabriel and Lirael.
890
Keywords: Magic -- Fiction; Fantasy